Investor Attention in Cryptocurrency Markets: Examining the Effects of Vaccination and COVID-19 Spread through a Wavelet Approach - Abida, Maher; Mnif, Emna (International Journal of Economics and Financial Issues, 2023)
The main goal of this paper is to determine how vaccination and the spread of COVID-19 have influenced investor interest in cryptocurrency. The paper quantifies the reproduction number of COVID-19 worldwide and in specific countries. It evaluates cryptocurrency volatility using various time scale frequencies by employing the Wavelet approach. Additionally, this research examines how investor interest in these sectors was impacted by immunizations and pandemic transmission. Our research demonstrates that during the COVID-19 epidemic, cryptocurrency volatility is greater across extended trade horizons and decreases following the introduction of immunizations. Furthermore, vaccination levels and the spread of COVID-19 significantly affect investor attention in the top three cryptocurrency markets. This work has several implications, such as highlighting the effect of COVID-19's spread in increasing the volatility of cryptocurrency markets and the role of vaccinations in reducing risks and increasing investor attention. The results of this study aid in forecasting bitcoin market activity and price movements, creating trading opportunities in the bitcoin market. The empirical findings will provide valuable insights for policymakers and investors, enabling them to develop better investment strategies. To the best of our knowledge, this study is the first to employ the R-number to calculate the effect of the COVID-19 vaccine and dissemination on cryptocurrency markets.